Textural and Physical Qualities of Starch Noodles Made from Heat-Moisture Treatment Canistel Starch (Pouteria campechiana) and Arrowroot Starch (Maranta arundinacea L.) - Pertiwi, Sri Rejeki Retna; Novidahlia, Noli; Apriani, Yasri; Aminullah, Aminullah (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Glosor noodles were generally made from palm sago starch; in this study, glosor noodles were made from HMT (Heat-Moisture Treatment) modified canistel starch and arrowroot starch. This study aimed to investigate the effect of the ratio between canistel starch and arrowroot starch on the physical and textural qualities of glosor noodles and to determine the selected product of HMT-modified canistel starch and arrowroot starch. This study used the one-factor Completely Randomized Design method, consisting of five levels of canistel starch and arrowroot starch, i.e 100:0%, 90:10%, 80:20%, 70:30%, and 60:40%. The textural properties of hardness, gumminess, springiness, and elongation percentage, as well as the physical properties of cooking loss, water absorption, and swelling power, were analyzed. The results showed that the higher the addition of arrowroot starch, the lower the springiness, cooking loss, water absorption, and swelling index of glossy noodles; however, the higher the hardness, gumminess, and elongation percentage. The chosen glosor noodle was HMT-modified canistel and arrowroot starch with a ratio of 70:30%. It had a hardness of 3,600 N, a gumminess of 1.391 N, a springiness of 0.778 mm, and a percent elongation of 275.938%. In addition, it also had a cooking loss of 5.462%, a water absorption capacity of 130.095%, and a swelling index of 12.19%.